(untitled) (Journal of Governance and Development (JGD), 2015)
The small and medium enterprises (SMEs) are the strongest foundation in Indonesia economy. In the end of 2012, SMEs in Indonesia reached 56.53 million units. This number contributed 59.08% of countryâ€™s GDP and 97.16% of employment opportunity (107 million people). As the real and strategic economy sector, SMEs have the highest resistance to face the global crisis. In their development, they faces some problems and weaknesses, such as financing, less-knowledge of marketing strategy, and intellectual rights. Indeed there are several concerned aspects in order to face the increasing competitiveness and satisfy the demand, such as standard and quality improvement, innovation and creativity challenges, output diversification, and stability of income. Nevertheless, SMEs in China have achieved rapid and sustainable growth for over the past three decades. They play a significant role in terms of any further reforms in shifting the components of Chinese economy toward the consumers. Chinese SMEs have gained an amazing expansion in terms of number and scale that exceeded 4.3 million in 2012 and the growth rate is steadily planned at 8%. The SMEs contributed also to 60% of countryâ€™s GDP, 50% of countryâ€™s tax revenues, 68% of exports, and provided more than 80% of employment opportunities in China. Strategies to reinforce the SMEs competitiveness in China are clusterization as a concept of â€œone village, one productâ€ or â€œone town, one industryâ€ and E-commerce trends. This paper seeks to analyze the institutional revitalization of SMEs to achieve global competitiveness and be resistant against the global crisis.